Invariant Approximation Property for Subgroups - Kannan, Kankeyanathan (Communications in Mathematics and Applications, 2021)
Analytic properties of invariant approximation property, studies analytic techniques from operator theory that encapsulate geometric properties of a group. We will study the invariant approximation property in various contexts. We shall show that it passes to subgroups.